Three-dimensional scanless holographic optogenetics with temporal focusing (3D-SHOT) - Nicolas C. Pégard (Nature Portfolio, 2017)
Optogenetics, the optical stimulation of neurons, suffers from many technical challenges that limit the number of neurons that can be excited as well as their relative positions. Here, Pégard et al. develop a method to simultaneously stimulate an arbitrary number of neurons in 3D space with single neuron resolution.